Komunikasi Simbolik dalam Tari Pendet Lanang pada Usabha Sambah di Desa Pakraman Pesedahan Kecamatan Manggis Kabupaten Karangasem - Ratna Pramesti Dasih, I Gusti Ayu (Institut Hindu Dharma Denpasar, 2018)
Communication can be done in a simple way to a complex way. The process of communication can be seen from the activities of social life so that the process of symbolic communications of society can be formed based on the meanings that are believed by himself then embodied with the symbols of communication. Dance Pendet Lanang acts as a communicator and village community Pakraman Pesedahan as a communicant. Communication process can occur in one direction or two way. The symbols contained in the Dance Pendet Lanang in the Village Pakraman Pesedahan has a uniqueness because the message conveyed has a sacred value that is believed and needs to be communicated to the public. Pendet Lanang Dance is one of the sacred dances that must be performed during the series of Usabha Sambah in Pakraman Pesedahan Village conducted every Purnama Fifth in accordance with the Balinese calendar system.